Analisis Pengembangan Aplikasi E-library Menggunakan Metode Agile - Muhammad Fadli Juliana Putra; Sopyan Hidayat (Journal of Information Systems and Business Technology, 2025)
Fast, flexible, and customizable information systems are essential in the ever-evolving digital era. The purpose of this study is to evaluate the Agile method in developing an E-Library application because this method has the ability to dynamically change user needs through an iterative and participatory process. In this project, the Agile method is used in six main stages, from gathering needs to assessment. The Black Box method is used to test the stability and suitability of the system's functions before being used with technologies such as PHP, MySQL, HTML, and Visual Studio Code. The results show that the Agile method can create an E-Library system that is responsive, effective, and in accordance with user requirements. The results of the system evaluation show that each feature runs well, and the application is considered to be able to improve the effectiveness of digital library management.